The Art of Seduction of Giacomo Casanova An Analysis of “The Story of My Life” - Helta Anggia (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
In “Histoire de ma vie” or what we know as “The Story of My Life”, by Giacomo Casanova, it was Casanova who was known as a womanizer or a great seducer to women. It was him who in almost of his life travelled from country to country to make his adventures which were fully colored with controversial affairs with different women. The first time he got an affair was with his instructor’s young sister, Bettina. “It was she who little by little kindled in my heart the first sparks of a feeling which later became my ruling passion”(36). From that on he made his way of connecting with different kinds of women until he felt that whatever gave pleasure to himself as the most important things in his life.